Sementes de piper cubeba nas dietas de alta e baixa digestibilidade para frangos de corte, uma alternativa de aditivo fitogênico - Domingues, Rodolfo Machado [UNESP] (2015)
Two experiments were conducted in the Poultry Section of the Universidade Estadual Paulista Júlio de Mesquita Filho (UNESP), School of Engineering Campus Ilha Solteira, both in the initial phase (1-21 days old) with the objective of evaluate the use of dried seeds of the Piper cubeba pepper as total or partial replacement to performance enhancers antibiotics and their effects on performance, serum biochemical profile, biometrics of the digestive tract and nutrient digestibility. Were used a total of 240 male broilers chicks, one day old Cobb strain in each experiment, being distributed in a completely randomized design, with five treatments and four replicates of 12 birds per experimental plot. The variables were subjected to analysis of variance and in case of statistical significance, the averages are compared by SNK test at 5% probability Experiment I evaluated the inclusion of Piper Cubeba in diets of high digestibility of the base corn and soybean meal. The performance and biochemical parameters were not affected by the use of pepper, but there was a reduction in the relative weight of the pancreas and increased ether extract digestibility. In the second experiment the diets were low digestibility based on corn, soybean meal and meat meal. The use of pepper has improved the digestibility of ether extract and did not affect performance and biometrics. Seeds of Piper cubeba not affect the performance and improve the digestibility of ether extract in diets of high and low digestibility